ENGLISH: Political Empowerment of Women: A Case Study of Women Participation in Governance of Balochistan Pakistan - Rehana Barkat; Prof. Dr. Muhammad Usman Tobawal (Al-Dalili, 2025)
The present research explores the facilitators and constraints to women’s political engagement and leadership in Balochistan, Pakistan, employing both survey and interview data. A series of qualitative research methods; including, questionnaires, focus group discussions, interviews and documentary review were used to capture socio-cultural related, economical and organizational barriers to women. This study shows that familistic-Patriarchal culture and gendered social practices and structures hinder women’s participation in governance a lot. Economic vulnerability and lack of resource rights, also increases non-recognition more so for women and especially those in the rural areas to engage in political activities. The paper thus revealed education as the power tool towards changing women, enhancing their status, attitudes to Work, and readiness towards leadership. However, lack of equal opportunities in accessing education is still a big setback. Measures like Community workshops, grass root organizations, scholarships to girls who want to study but are prohibited by their parents in such areas become workable strategies. Further, the direction of micro financing along with social entities at community level is emphasized for enhancing the fairness in socio-economic and political spheres especially in rural areas. This apparently shows that institutional challenges still exist even with enhancement strategies like gender quotas and reserved seats. Lack of stringent measures and low nomination of women for higher leadership political posts are evident to argue for structural change. Therefore, the study suggests that policy enforcement should be strengthened, leadership must be trained, and the organization’s culture must be changed so that women can have an active role in governance. The study shows that there is a close relationship between economic status, education, and politics. Efforts to increase women’s agencies have the potential to produce meaningful, long-term improvements in governance, such as improved policy compared to health, education and welfare. Thus, this research ushers hope for policymakers, nonprofits, and community actors interested in the improvement of women’s political participation across various nations and regions by attending to socio-cultural and institutional constraints. The study therefore reaffirms the need for both policy reforms and education and community mobilization to enhance gender balance at the leadership level.